Ethnography Of Communication In Arabic Language Learning - Rudiny Indis; Mehdi Ahmed (UIN ANTASARI, 2022)
This research was the Ethnography of Communication in Arabic learning to students MA Ubudiyah Bati-Bati. This study started from the author's initial observation about the tradition of many of the 12th-grade students in Arabic learning communication at MA Ubudiyah Bati-Bati found language traditions. These traditions were unique in communication between teachers to students, students to students, and students to teachers. As with the diverse ethnic backgrounds of students. Based on the statement above, the results of this study indicate that educational experience, ethnicity, place of residence, and language use of these affect students' communication style in the classroom. Furthermore, in this study, students used 5 languages in communication in the classroom: Arabic, Banjarese, Indonesian, English, and Javanese. Then the speech patterns of student interactions in this study amounted to 16 patterns of interaction speech used. A pattern in the exchange of learning Arabic. Produces this pattern more from teachers to students because, in it, there are questions and answers. For students to students, there are only a few because they do not have much time to talk to their friends in the class room when learning Arabic. In addition from the results of the analysis of interactions that occurred in learning Arabic, the researchers found 3 words that were often spoken during the learning process until students became accustomed to saying them. That is, “Bujurlah pa”, “Insya Allah”, and “Izin bertanya/izin menjawab”.